Prevalence of high blood pressure in Brazilian adolescents and quality of the employed methodological procedures: systematic review - Magalhaes, Marina Gabriella Pereira De Andrada; Oliveira, Luciano Machado Ferreira Tenorio De; Christofaro, Diego Giulliano Destro; Ritti-dias, Raphael Mendes (Associação Brasileira de Pós -Graduação em Saúde Coletiva, 2013)
OBJETIVO:Revisar a literatura sobre estudos que estimaram a prevalência de pressão arterial elevada (PAE) ou hipertensão arterial sistêmica (HAS) em adolescentes brasileiros, considerando os procedimentos metodológicos empregados.MÉTODOS:Pesquisa bibliográfica de estudos de prevalência de PAE/HAS em adolescentes de 1995 a 2010. A busca foi realizada nas bases de dados eletrônicos PubMed/Medline, Lilacs, SciELO, Isi e Adolec. Foram utilizados os descritores: hipertensão, pressão arterial, adolescente, estudantes, estudos transversais, prevalência e Brasil, nas línguas portuguesa e inglesa. Além disso, foi elaborado um escore, baseado nas Recommendations for Blood Pressure Measurement in Humans and Experimental Animals e nas VI Diretrizes Brasileiras de Hipertensão, para a análise dos procedimentos utilizados para medida da PA nos estudos variando de 0 a 18.RESULTADOS:Foram identificados 21 artigos, a maioria publicada nos últimos 10 anos, sendo 90,5% realizados em base escolar e nas regiões sudeste, nordeste e sul do país. As prevalências de PAE/HAS variaram de 2,5 a 30,9%. A pontuação dos estudos variou de 0 a 16. Foi observada uma correlação negativa significante (rho = -0,504; p = 0,020) entre a prevalência de PAE/HAS e o escore da qualidade da medida da PA.CONCLUSÃO:A grande variabilidade das estimativas da PAE/HAS parece ser influenciada pelos procedimentos metodológicos utilizados nos estudos.

OBJECTIVE:To review the literature on studies that estimated the prevalence of high blood pressure (HBP) or systemic arterial hypertension (SAH) in Brazilian adolescents, considering the employed methodological procedures.METHODS:Bibliographical research of prevalence studies of HBP/SAH in adolescents from 1995 to 2010. The search was conducted in the electronic databases PubMed/Medline, Lilacs, SciELO, and Isi Adolec. The descriptors hypertension, BP, teen, students, cross-sectional, prevalence and Brazil were used in Portuguese and English. Furthermore, a score ranging from 0 to 18 based on Recommendations for Blood Pressure Measurement in Humans and Experimental Animals and the VI Brazilian Guidelines of Hypertension was elaborated, in order to analyze the procedures used to measure BP in studies.RESULTS:Twenty-one articles were identified, mostly published in the last 10 years, and 90.5% were performed in school-based and regions of the Southeast, Northeast and South. The prevalence of HBP/SAH ranged from 2.5 to 30.9%. The score of the studies ranged from 0 to 16. A significant negative correlation (rho = -0.504; p = 0.020) was observed between the prevalence of HBP/SAH and the score of BP measurement quality.CONCLUSION:The great variability of PAE/SAH estimates appears to be influenced by methodological procedures used in the studies.
Prevalencia de pressao arterial elevada em adolescentes brasileiros e qualidade dos procedimentos metodologicos empregados: revisao sistematica
Keywords: Adolescente; Hipertensao; Pressao arterial; Estudantes; Revisao; Brasil; Adolescent; Hypertension; Arterial pressure; Students; Review; Brazil